Leydig cell tumor in the post-menopausal woman: case report and literature review - Sherf, Sahar; Martinez, Dorothy (Acta Biomedica Atenei Parmensis, 2017)
Leydig cell tumors of the ovary account for less than 0.1% of all ovarian tumors (1). We present two cases in which patients had markedly elevated serum testosterone levels and frank hirsutism. Both cases revealed right ovarian Leydig cell tumors upon oophorectomy with post-surgical resolution of hypertestosteronemia. While rare and difficult to diagnose, androgen secreting tumors should be suspected in women with hyperandrogenism and hirsutism, especially in the postmenopausal population.